Guidance and Counseling Perspective Da'wah: Implications of Madrasah Guidance and Counseling Services To Prevent Child Marriage In Central Lombok District - Lalu Abdurrachman Wahid (TASAMUH, 2023)
This research aims to describe the general picture of the implementation of BK services in Madrasas, analyze what factors inhibit the implementation of BK services, and describe what efforts have been made to overcome obstacles to the implementation of BK services in Madrasas to prevent child marriage in Central Lombok Regency. This research approach is qualitative with descriptive research type. The location of this research is MAN 1 Central Lombok and MTsN 1 Central Lombok. The primary data source for this research is through observation and interviews with students, guidance and counseling teachers, and madrasah leaders as well as secondary data sources through documentation. Furthermore, data analysis techniques in this research were carried out by reducing data, presenting data, verifying data and drawing conclusions. The results of this research describe the general picture of guidance and counseling services in madrasas to prevent child marriage, namely through basic services, individual specialization and planning services, responsive services, and system support. Internal factors inhibiting the implementation of guidance and counseling services in madrasas include the competency of guidance counselors which is still lacking and needs to be upgraded further, the inadequate work experience of guidance counselors , the state of health and age, the motivation and work discipline of guidance counselors, and the planning and implementation of counseling services which are less than optimal. Furthermore, external factors that hinder include inadequate facilities and infrastructure, lack of coordination between madrasah leaders and local governments and related institutions, the lack of guidance and counseling teachers, the economic disadvantage of guidance and counseling teachers, and the lack of awareness and participation of students and parents. Lastly, guidance and counseling teachers and madrasah leaders have made efforts to overcome obstacles in implementing the guidance and counseling service program in madrasas to prevent child marriage. To reduce the number of cases of child marriage, there needs to be cooperation from all school personnel and external parties such as parents and related institutions to jointly prevent the practice of child marriage involving students.